Inventory and Description of Macroalgae In Rambut Island Kepulauan Seribu DKI Jakarta - Sri Handayani (Journal of Tropical Biodiversity, 2022)
Macroalgae is a marine biological resource that has the potential to be developed because macroalgae have an important role both in terms of ecology and economy. But anthropogenic pressures such as domestic waste, solid waste disposal, urban community activities, urban planning development activities, and community activities in the waters tend to affect macroalgae growth and diversity which even cause damage to the extinction of macroalgae species. This research needs to be done as the limited information about macroalgae on Rambut Island. The purpose of this study was to determine the composition, and diversity by inventorying and describing the types of macroalgae and to analyze the state of the macroalgae community structure in the Rambut Island waters. Data and information on types and descriptions of macroalgae morphology can be used as a basis for managing and enriching macroalgae biodiversity, especially on Rambut Island, Kepulauan Seribu. The methodology is the quadratic transect method. The results obtained 28 species belonging to 3 divisions, namely 18 species of Chlorophyta, 5 species of Phaeophyta, and 5 species of Rhodophyta. The diversity index of macroalgae is moderate (1.73) and there are no dominant species. The quality of the waters in Rambut Island supports the growth of macroalgae. The macroalgae community structure in Rambut Island is still in a stable condition.